Hyperbolical discounting and endogenous growth - Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2013)
This paper provides the exact analytical solution for the standard model of endogenous growth when consumers have present-biased preferences and make time-inconsistent savings plans, which they revise continuously. It is shown that long-run growth is not necessarily lower under present-biased preferences. In fact, an equivalence result holds. If hyperbolical discounting provides the same present value of a constant infinite income stream as standard exponential discounting, then the equilibrium rate of economic growth is also the same under both discounting methods. In this sense present-bias and the entailed time-inconsistency of savings plans are harmless for economic growth. The result is robust to the introduction of non-homothetic utility and a variable elasticity of intertemporal substitution in consumption.
Keywords: D91; E21; O40; 330; hyperbolic discounting; time-inconsistency; endogenous growth; adjustment dynamics